Developing Approaches to Critical Management Studies in the Netherlands. - Letiche, Hugo (Critical Perspectives on International Business.)
An alternative approach to critical management studies out of the Netherlands. There organization studies has not broken away from philosophy and is not an independent social science. More sympathetic to practitioners this collection of papers provides a very different view.